Analysis of Factors Influencing The Quality of Pharmaceutical Services At Pharmacy Outlets in Kotamadya Tangerang - Yari, Cut Ervinar; Delina Hasan, Delina; Jannah, Syarifah Miftahul El (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2023)
Pharmaceutical services at pharmacies in several regions of Indonesia are still low, that is un-equal to the growth of the establishment in pharmacies which continues to increase. The four sub-sectors which coverage in pharmaceutical services include non-prescription drug service standards, KIE services, and prescription service and drug management standards in pharmacies. This cross-sectional study was carried out in Tangerang area to determine the factors that influence the quality of pharmaceutical services, with a total of 68 pharmacists serving in 68 pharmacies. The characteristics of pharmacists are conducting by using questionnaire and observation. The results obtained for APA characteristics were 72.1% with age 26-35 years, 80.9% female, 94.1% having undergraduate and professional degree, and 98.53% had worked as APA ≤ 10 years. The quality of pharmaceutical services is 48.5% in the good category and the pharmacist (APA) presence factor is the most dominant variable that influencing the quality of pharmaceutical services (OR-58.3 with p-value=0.002), while the ones which not affecting are APA motivation and pharmacy ownership status (p> 0.05).